Minimalist parsing - Berwick, Robert C.; Stabler, Edward P. (Oxford, United Kingdom ; New York, NY : Oxford University Press, 2019)
This book is the first dedicated to linguistic parsing - the processing of natural language according to the rules of a formal grammar - in the Minimalist Program. While Minimalism has been at the forefront of generative grammar for several decades, it often remains inaccessible to computer scientists and others in adjacent fields. This volume makes connections with standard computational architectures, provides efficient implementations of some fundamental minimalist accounts of syntax, explores implementations of recent theoretical proposals, and explores correlations between posited structures and measures of neural activity during human language comprehension. These studies will appeal to graduate students and researchers in formal syntax, computational linguistics, psycholinguistics, and computer science.
Machine generated contents note: 1. Minimalist parsing / Edward P. Stabler -- 1.1.A perspective on language and parsing -- 1.2. This volume -- 1.3. Minimalist-inspired formalisms -- 1.4. Conclusion -- 2. Towards a Minimalist Machine / Jason Ginsburg -- 2.1. Introduction -- 2.2. Free or feature-driven movement -- 2.3.Computational cyclicity -- 2.4. Architecture overview -- 2.5. Fundamental operations -- 2.6. The decision procedure P -- 2.7. Non-determinism revisited -- 2.8.Computational cyclicity revisited -- 2.9. Further remarks and conclusions -- 3.Combining linguistic theories in a Minimalist Machine / Sandiway Fong -- 3.1. Introduction -- 3.2. Multiple Agree (Chomsky 2001) -- 3.3. Expletives (Chomsky 2001) -- 3.4. Thematization/Extraction (Th/Ex) (Chomsky 2001; Sobin 2014) -- 3.5. That-trace effects and subject vs. object wh-movement (Pesetsky and Torrego 2001) -- 3.6. Relative Clauses (Pesetsky and Torrego 2001; Gallego 2006) -- 3.7. Conclusion -- 4. Parsing with Minimalist Grammars and prosodic trees / Kristine M. Yu -- 4.1. Introduction -- 4.1.1. Previous work on prosodically informed syntactic parsers -- 4.1.2. The syntax-prosody interface -- 4.2. Samoan syntax, spellout, prosody, and interfaces: background -- 4.2.1. Samoan syntax and spellout -- 4.2.2. Samoan prosodic constituency -- 4.2.3. The Samoan syntax-prosody interface -- 4.3. Samoan syntax, spellout, prosody, and interfaces: implementation -- 4.3.1. Generation of candidate prosodic parses with an xfst transducer -- 4.3.2. Syntactic/post-syntactic grammar fragment: MG lexicon and derivation -- 4.3.3. Simultaneous (post- )syntactic parsing and MatchPhrase computation -- 4.3.4. Final phonological transduction after MG parse: StrongStart -- 4.4. Discussion and conclusion -- 5. Parsing ellipsis efficiently / Gregory M. Kobele -- 5.1. Introduction -- 5.2. Ellipsis in minimalist grammars -- 5.2.1. Minimalist grammars -- 5.2.2. Derivational structure -- 5.2.3. Ellipsis -- 5.2.4. Hypothetical derivations -- 5.2.5. Ellipsis operations -- 5.2.6. Interpreting ellipsis -- 5.2.7. An example -- 5.3. The complexity of ellipsis resolution -- 5.3.1. Parsing in the presence of ellipsis -- 5.3.2. Resolving ellipsis -- 5.3.3. Updating the discourse context -- 5.3.4. Eliding maximal projections -- 5.3.5. Bounding ellipsis -- 5.3.6. Stopping silence -- 5.4. Conclusion -- 6. Left-corner parsing of minimalist grammars / Tim Hunter -- 6.1. Human processing of long-distance dependencies -- 6.1.1. Empirical background -- 6.1.2. Retrieval decisions as ambiguity resolution -- 6.2. The top-down MG parser -- 6.3. Towards a left-corner MG parser -- 6.3.1. CFG left-corner parsing -- 6.3.2. Basic cases -- 6.3.3. Multiple movements -- 6.4. Dealing with remnant movement -- 6.4.1. An outline of the challenge -- 6.4.2. Outline of a candidate solution -- 6.5. Empirical connections based on what we have so far -- 6.5.1. Active gap-filling -- 6.5.2. Island sensitivity -- 6.6. Conclusion -- 7. Grammatical predictors for fMRI time-courses / John Hale -- 7.1. Introduction -- 7.2. Parameters in neuro-computational models of sentence processing -- 7.2.1. Grammar -- 7.2.2. Parsing strategy -- 7.2.3.Complexity metrics -- 7.2.4. Summary -- 7.3. Other factors influencing sentence processing -- 7.3.1. Word-to-word associations -- 7.3.2. Lexical-semantic coherence -- 7.4. Correlating fMRI time-courses with various metrics during natural story listening -- 7.4.1.Complexity metrics -- 7.4.2. Data acquisition -- 7.4.3. Data analysis -- 7.4.4. Results -- 7.5. Towards a functional anatomy of sentence comprehension.
Includes bibliographical references and index.
Keywords: Parsing (Computer grammar); Grammar, Comparative and general -- Parsing; Minimalist theory (Linguistics); Analyse automatique (Linguistique); Analyse grammaticale; Grammar, Comparative and general -- Parsing; Parsing (Computer grammar); Essays